Dependence of sapphire hardness on loading type and orientation - Sinani, A.B.; Dynkin, N.K.; Konevskiy, P.V.; Lytvynov, L.A. (Functional Materials, 2009)
The mechanical strength of sapphire in different crystallographic diorections has been studied within a wide loading range. A correlation has been found between the resistance to hig-speed shock and the sapphire crystallography.